Scleral burn and perforation following transscleral cyclophotocoagulation - Beau Billings; Drew B. Fletcher; Alex C. Weaver; Mohammad Tahseen Alkaelani; Kyle Fallgatter; Ramen Daneshvar (American Journal of Ophthalmology Case Reports, 2023)
Purpose: This case report highlights scleral perforation as a complication of diode laser transscleral cyclophotocoagulation in the treatment of refractory primary open-angle glaucoma, as well as the management of this complication. Observations: A 78-year-old woman with primary open-angle glaucoma refractory to medication had transscleral cyclophotocoagulation performed in her left eye. During the procedure, it was noted that conjunctival burns and scleral perforation had occurred, at which point the procedure was aborted. Limited peritomy and patch graft with split-thickness donor cornea was done in the area of the scleral thinning and perforation. The patient had a good outcome with an intraocular pressure of 8 mm Hg, appropriate integration of the patch graft, and no significant conjunctival inflammation at the 2-month post-operative visit. Conclusions and importance: This patient, without any known risk factors for scleral thinning or necrosis, experienced conjunctival burn as well as scleral perforation during transscleral cyclophotocoagulation, underscoring this possible complication of the procedure. Additionally, split-thickness donor cornea was used to patch graft the area of scleral thinning and perforation, which is a method of managing this complication that had not been previously reported.